The Types and Meaning of Paradox Found in the Poems of Rudyard Kipling’s - Krisna, I Putu Henry Adi; Jayantini, I G A Sri Rwa; Resen, I Wayan (Journal of Language and Applied Linguistics, 2023)
When writing a piece of art work called poetry, the poets often utilize figurative language to express their ideas and feelings. Figurative language will beautify the poetry of which the readers will put their interests. Typically, figurative language in a poem includes paradox to emphasize the poem’s meaning. This research focuses on types and meaning of paradox in the Rudyard Kipling’s selected poem. The study uses a descriptive qualitative method in analyzing the figure of speech in Rudyard Kipling’s selected poems. The research found 17 (seventeen) of paradoxes consist of 7 (seven) rhetorical paradox, 7 (seven) social paradox, 2 (two) logical paradox and 1 (one) philosophy of science paradox. The rhetorical and social paradoxes are the most current paradoxes in Kipling's poem, according to the research on paradox in the poem. The notion of each phrase to which they belong, as well as the meaning of the paradox, are used to define the interpretations of paradox. In Kipling's poem, paradox was exploited to make lines more colourful, inventive, and meaningful. These are there to bring clarity, colour, and persuasion to the novel.